(untitled) (Journal of Nepal Geological Society, 2013)
The quartz schist in the Indus-Yarlung Tsangpo suture zone, from Namche Barwa, east Himalaya undergone extensive mylonization with well developed, foliation and lineation; its S-C fabric, "σ" and "δ" type porphyroblasts and asymmetrical folds indicate the northwestward normal slip ductile shear deformation. The electron backscattered diffraction (EBSD) data, lattice preferred orientation (LPO) patterns for quartzes in the matrix foliation (or external foliation, S) and inclusion-trails in the rim of the garnet porphyroblasts (S) both show a top-to-NW (normal) shear sense. While LPO patterns for quartzes of the inclusion-trails in the garnet porphyroblast cores (S) show an opposite shear sense (top-to-SE). The garnet compositional zonation indicates a growth zoning characteristic from energy dispersive spectroscopy (EDS) analysis. By connecting the inclusion-trails in garnet cores, an initial foliation trace with asymmetrical fold shape can be obtained. It suggests that these garnet porphyroblasts with snov, ball structure formed on the asymmetrical folds by the rotation of external shear sense rather than the rotation of garnet porphyroblasts. Gamet porphyroblast with snowball structure proposed that the rocks from the lndus Yarlung Tsangpo suture zone west side of the Namche Barwa syntaxis have undergone southeastward thrusting and later followed by northwestward normal slipping.